Exploring yearly vocational graduate career development, article citation and top publications - Aghniya, Salsabila Manna; Nofri, Bunga Arnelia; Saadah, Nur Aini; Ayu, Mahesa; Handayani, Mustika Nuramalia (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2024)
There has been a lot of research on career development, including during the COVID-19 period, but the number of studies that specifically analyze related developments from year to year is increasingly limited. This study aims to determine the development of research that focuses on career development of vocational graduates by using the bibliometric analysis method. The analysis was conducted by collecting articles published in Scopus indexed journals. Publication data collection was carried out using Scopus journals. VOSviewer application to create bibliometric network visualization. The results of the analysis show that the United States is a country that contributes the largest number of publications that discuss career development in the world. Center for International Research on Education Systems, Victoria University, Melbourne, Australia is the first institution to publish about career development among the top 10 institutions.